Global Seismic Noise Entropy - Lyubushin, Alexey (Frontiers in Earth Science, 2020)
Data of continuous records of low-frequency (periods from 2 to 1000 minutes) seismic noise on a global network of 229 broadband stations located around the world for 23 years, 1997-2019, is analyzed. The daily values of the entropy of the distribution of the squares of the orthogonal wavelet coefficients are considered as an informative characteristic of noise. An auxiliary network of 50 reference points is introduced, the positions of which are determined from the clustering of station positions. For each reference point, a time series is calculated, consisting of 8400 samples with a time step of 1 day, the values of which are determined as the medians of the entropy values at the 5 nearest stations that are operable during the given day. The introduction of a system of reference points makes it possible to estimate temporal and spatial changes in the correlation of noise entropy values around the world. Estimation in an annual sliding time window revealed a time interval from mid-2002 to mid-2003, when there was an abrupt change in the properties of global noise and an intensive increase in both average entropy correlations and spatial correlation scales began. This trend continues until the end of 2019 and it is interpreted as a feature of seismic noise which is connected with an increase in the intensity of the strongest earthquakes, which began with the Sumatran mega-earthquake of December 26, 2004, M=9.3. The values of the correlation function between the logarithm of the released seismic energy and the bursts of coherence between LOD and the entropy of seismic noise in the annual time window indicate the delay in the release of seismic energy relative to the coherence maxima. This lag is interpreted as a manifestation of the triggering effect of the irregular rotation of the Earth on the increase in global seismic hazard.